THE INFLUENCE OF HALAL LABELS AND PRICES ON PURCHASE DECISIONS FOR MIXUE PRODUCTS: STUDY OF FEB UMSU STUDENTS - Putra, Rezza Asmara; Affandy Nst, Satria Mirsya (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to find out how the halal label and price variables influence purchasing decisions, both partially and simultaneously, for Mixed products (case study of students at Muhammadiyah University, North Sumatra). This research approach is associative. The population is 100 users and the sample is 100 mixed consumers. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. It is partially known that the halal label has a significant influence on purchasing decisions for mix products. In particular, it is known that price has a significant influence on purchasing decisions for mix products. Simultaneously, it is known that the halal label and price have a significant influence on purchasing decisions for mix products.